2005
DOI: 10.1007/s00024-005-2711-x
|View full text |Cite
|
Sign up to set email alerts
|

Depth Estimates for Slingram Electromagnetic Anomalies from Dipping Sheet-like Bodies by the Normalized Full Gradient Method

Abstract: The Normalized Full Gradient (NFG) method was proposed in the mid-1960s and was generally used for the downward continuation of the potential field data. The method eliminates the side oscillations which appeared on the continuation curves when passing through anomalous body depth. In this study, the NFG method was applied to Slingram electromagnetic anomalies to obtain the depth of the anomalous body. Some experiments were performed on the theoretical Slingram model anomalies in a free space environment using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…The degree of the NFG can be taken as 1, 2, 4, etc. m = 1 is generally used for potential field (AYDıN, 1997a) and electromagnetic data (DONDURUR, 2005) as is the case for the present study. Higher order values of the degree of the NFG were applied in seismic applications effectively by KARSLI (2001) using the width of the recorded signal to improve seismic resolution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The degree of the NFG can be taken as 1, 2, 4, etc. m = 1 is generally used for potential field (AYDıN, 1997a) and electromagnetic data (DONDURUR, 2005) as is the case for the present study. Higher order values of the degree of the NFG were applied in seismic applications effectively by KARSLI (2001) using the width of the recorded signal to improve seismic resolution.…”
Section: Introductionmentioning
confidence: 99%
“…AYDıN (1997a), DONDURUR (2005) and KARSLI (2001) suggested that l = 1 or 2 gives reasonable results in the downward continuation, therefore, l = 1 is used in this study. In addition, the harmonic interval in equations (2), (7) and (8) is restricted to a lower limit of N 1 and an upper limit of N 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method eliminates the side oscillations which appeared on the continuation curves when passing through an anomalous body depth (Dondurur 2005;Sindirgi et al 2008;Aghajani et al 2009;Abedi et al 2012). The NFG operator G h x; z ð Þ constitutes the basic concept of the NFG method and is defined in two dimensions as…”
Section: Normalized Full Gravity Gradient Imagingmentioning
confidence: 99%
“…Areas of which normalized full gradient values are higher than 1, determine the localization of the structure (DONDURUR 2005;detailed in DONDURUR 2005;AYDIN 2007) In order to test the efficiency of the NFG method was applied to gravity effects of two cubes. For all of the three simple theoretical models, the profile length is chosen as 500 m while the structural locations of the models correspond to the midpoints of the profiles.…”
Section: )mentioning
confidence: 99%